A meta-analysis of the relationship between anatomical variations of pulmonary veins and atrial fibrillation. Issue 1 (2nd January 2020) - Cheruiyot, Isaac; Munguti, Jeremiah; Olabu, Beda; Gichangi, Peter
Abstract: Background: Our aim was to provide an evidence-based assessment of the relationship between pulmonary vein variants and atrial fibrillation (AF). Methods: A comprehensive systematic search was performed on the databases PubMed, EMBASE, Cochrane library and Science Direct. Following assessment of eligibility and methodologic quality, data on PV variants were extracted and pooled into a meta-analysis. Results: A total of 12 studies (1337 cases and 1250 controls) were included. Presence of a right middle pulmonary vein was significantly associated with AF (OR = 1.85, 95% CI 1.26–2.72, p  = .002). No significant association was however noted between presence of a common pulmonary vein ostia and AF. In the analysis of ostial diameters, the strongest association was observed between increased left common ostia diameter and AF (OR = 2.71, 95% CI 0.99–4.44, p  = .002), followed by right superior (OR = 2.39, 95% CI 1.76–3.02, p  < .00001), left superior (OR = 2.30, 95% CI 1.48–3.13, p  < .00001), right inferior (OR = 2.19, 95% CI 1.69–2.69, p  < .00001) and left inferior (OR = 1.79, 95% CI 1.25–2.34, p  < .00001) pulmonary veins. Conclusion: The findings of the current study support the hypothesis that pulmonary vein variations predispose to AF. Further studies into the role of structural abnormalities of the pulmonary veins variations in the genesis of AF are recommended.